Tomb in Duleek Church Co.y Meath - Grose, Daniel, approximately 1766-1838 (1792)
Sketch of an effigy of a bishop holding a crozier in his left hand, from the abbey of Duleek, County Meath, Ireland.
Inscribed in ink l.c.: Reduced on the Miscels. Plate.
Inscribed in ink on verso of drawing: Reduced 9th September 1792.
Inscribed in pencil on verso of drawing: [Tomb?] in Duleek Church.
Title inscribed in ink u.c..
Probable attribution to Lieutenant Daniel Grose, (ca. 1766-1838).
Irish Topographical prints & drawings / Rosalind M. Elmes. - Malton Press, Dublin, 1975
Keywords: Tombs & sepulchral monuments -- Ireland -- Duleek -- 1790-1800.; Ink drawings -- Irish -- 1790-1800.; Wash drawings -- Irish -- 1790-1800.